Measuring Human Capital Indicators in Iraq for 2010-2012 - Al-Dabash, Abduallah Hamad; Muhammad, Nishteman Hassan (Journal of University of Human Development, 2016)
Reflect the work on his mental capacity and muscle enjoyed by the man, and used for the production of goods and services strength. Meaning that the labor force constitutes the total forces that contribute and produce various goods and services in the community, and human capital is all the knowledge and capacity- and skills that Acquisition humans in society through education and practical experience, hypotheses of the study: "The human capital indicators in Iraq with low values and that the promise of the government's attention or develop the skills, knowledge and capabilities of human capital of the private sector to contribute effectively in the production and productivity and economic development of the country. objectives of the study: the research concluded: human capital in Iraq indicators show that it is very low, except illiteracy indicator that the high rate of illiteracy among the shows ages 15 and above, and this age group is young and active power economically . low skills and capabilities of the Iraqi workforce and the weakness of its contribution in the areas of creativity, innovation and the associated weakness of education and the adoption of theoretical education and lack of negligent or practical levels of education or applied, which weakens the contribution to economic development capabilities. suffers head Iraqi human capital of neglect in the areas of training, rehabilitation and keep pace with global scientific and technological developments . Which led to the migration of Iraqi scientific talent to other countries to prove its Scientific and its place among the global labor force He suggested: improving the conditions of human capital, especially in the production of educational institutions. And through the development of training methods and the development of skills and attention to the practical aspects of the study. Must develop human capital are geared for practical purposes and appropriate to meet the needs of the short and long-term community. Strengthening the trend towards higher education scientific and practical studies in order to achieve development objectives and requirements of trained human resources.